2020
DOI: 10.36108/pajols/0202/40(0310)
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Tuber Peels of Tacca leontopetaliodes on the Biochemistry and Histology of Gills and Liver of Clarias gariepinus Juveniles

Abstract: Background: Increased rate of water pollution has detrimental effects on the health of fish and other aquatic organisms. This invariably affects humans by causing food insecurity, hunger and poverty. In an effort to curb this menace, this study investigated the effects of crude tuber peel extract of Tacca leontopetaliodes on the biochemical and histological parameters of Clarias gariepinus. Methods: Acute toxicity (96 hr . LC50) test was conducted after a range finding test from which definitive test concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Abalaka et al [21] reported hyperemia and severe oedema with lamellae fission of the gills of C. gariepinus exposed to stem bark ethanol extract of Adenium obesum. Audu et al [22] reported an increase in gills histopathological alterations (mild, moderate to severe lamellae cell depletion) in C. gariepinus juveniles with increased concentration of tuber peel extract of Tacca leontopetaliodes. Similar histopathological changes have been reported in the gills of O. niloticus fingerlings after exposure to acute concentrations of B. aegyptiaca [23].…”
Section: Introductionmentioning
confidence: 99%
“…Abalaka et al [21] reported hyperemia and severe oedema with lamellae fission of the gills of C. gariepinus exposed to stem bark ethanol extract of Adenium obesum. Audu et al [22] reported an increase in gills histopathological alterations (mild, moderate to severe lamellae cell depletion) in C. gariepinus juveniles with increased concentration of tuber peel extract of Tacca leontopetaliodes. Similar histopathological changes have been reported in the gills of O. niloticus fingerlings after exposure to acute concentrations of B. aegyptiaca [23].…”
Section: Introductionmentioning
confidence: 99%